Propose Framework: How is the Influence of Culture-Moderated Corporate Governance on the Implementation of Enterprise Risk Management in Companies? - Matias Andika Yuwono; Lena Ellitan (CV. ULIL ALBAB CORP, 2024)
Corporate Governance (CG) is a core concept in modern corporate strategy, especially in the banking industry. This article examines the relationship between implementing CG, Enterprise Risk Management (ERM), and organizational culture in the banking context. The research background details the impact of technological change, globalization, and transactions on enterprise risk management challenges. Lack of adequate governance was a significant cause of corporate bankruptcies and financial crises, particularly the 2008-2009 crisis. The research explains how effective CG implementation can influence ERM and how organizational culture is crucial in aligning ERM with the company's internal values and norms. This proposed research framework shows that effective CG positively impacts the company, creating a solid foundation for managing risks wisely. A positive organizational culture is also a critical factor in ERM effectiveness. Harmonious integration between CG, ERM, and organizational culture is the primary key to achieving full effectiveness of ERM implementation. It was found that good governance creates benefits such as integrated risk management, clear leadership structures, openness, robust oversight systems, compliance, reputational benefits, risk-based decision-making, and an emphasis on innovation.